2017
DOI: 10.3390/ijms18020445
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging for Initial Staging and Therapy Assessment in Multiple Myeloma Patients

Abstract: Multiple myeloma (MM) is a hematological neoplasm characterized by the clonal proliferation of malignant plasma cells in the bone marrow. MM results in diffuse or focal bone infiltration and extramedullary lesions. Over the past two decades, advances have been made with regard to the diagnosis, staging, treatment, and imaging of MM. Computed tomography (CT) and magnetic resonance imaging (MRI) are currently recommended as the most effective imaging modalities at diagnostic. Yet, recent data from the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) is currently recommended as the most effective imaging for MM at diagnosis [ 2 ]. Positron emission tomography (PET) combined with computed tomography using [ 18 ]Fluorodeoxyglucose ( 18 F-FDG) is still being evaluated for initial staging and therapeutic monitoring in this pathology and its place needs to be validated [ 3 , 4 ]. However, 18 F-FDG being a non-tumor-specific metabolic tracer, development of phenotype tumor PET imaging is an attractive novel option to improve tumor characterization by targeting biomarkers expressed by neoplasm’s cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is currently recommended as the most effective imaging for MM at diagnosis [ 2 ]. Positron emission tomography (PET) combined with computed tomography using [ 18 ]Fluorodeoxyglucose ( 18 F-FDG) is still being evaluated for initial staging and therapeutic monitoring in this pathology and its place needs to be validated [ 3 , 4 ]. However, 18 F-FDG being a non-tumor-specific metabolic tracer, development of phenotype tumor PET imaging is an attractive novel option to improve tumor characterization by targeting biomarkers expressed by neoplasm’s cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has seen the growing use of PET using 18 F-fluorodeoxyglucose (FDG-PET) for the staging and assessment of therapy in multiple myeloma (1,2). Several studies have shown the prognostic value of this imaging technique.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the Durie–Salmon Plus (DS Plus) staging system integrated new imaging techniques, such as 18 F-2-fluoro-2-deoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) and magnetic resonance imaging (MRI), into a new generation of MM staging and offered the opportunity to precisely stage patients by anatomic and functional techniques [ 8 ]. 18 F-FDG PET/CT provides prognostic information on symptomatic MM at the baseline and therapeutic follow-up, allowing the detection of extramedullary disease (EMD) [ 9 ]. However, no standard interpretation criteria have been proposed for the evaluation of 18 F-FDG PET/CT scans in MM, preventing reproducibility of data.…”
Section: Introductionmentioning
confidence: 99%